Tat peptide-admixed elastic liposomal formulation of hirsutenone for the treatment of atopic dermatitis in Nc/Nga mice - Kang MJ; Eum JY; Jeong MS; Park SH; Moon KY; Kang MH; Kim MS; Choi SE; Lee MW; Lee DI; Bang H; Lee CS; et al. (International Journal of Nanomedicine, 2011)
Myung Joo Kang1, Jae Yoon Eum1, Mi Sook Jeong2, Sang Han Park1, Ki Young Moon1, Mean Hyung Kang1, Min Soo Kim1, Sun Eun Choi1, Min Won Lee1, Do Ik Lee1, Hyoweon Bang2, Chung Soo Lee2, Seong Soo Joo3, Kapsok Li2, Mi-Kyung Lee2, Seong Jun Seo2, Young Wook Choi11College of Pharmacy, ChungAng University, Heuksuk-dong, Dongjak-gu, Seoul, 2College of Medicine, Chung-Ang University, Heuksukdong, Dongjak-gu, Seoul, 3Division of Marine Molecular Biotechnology, Gangneung-Wonju National University, Gangneung, South KoreaBackground: The aim of the present study was to enhance a topical delivery of hirsutenone (HST), a naturally occuring immunomodulator, employing Tat peptide-admixed elastic liposomes (EL/T).Methods: HST-loaded EL, consisting of phosphatidylcholine and Tween 80 (85:15 w/w%), were prepared using thin film hydration method. By adding Tat peptide to EL (0.16 w/w%), EL/T were formulated. The in vitro skin permeation of HST was examined using a Franz diffusion cell mounted with depilated mouse skin. Lesions for atopic dermatitis (AD) were induced by a topical application of diphenylcyclopropenone to NC/Nga mice. Therapeutic improvements of AD were evaluated by clinical skin severity scores. Immunological analyses on inducible nitric oxide synthase and cyclooxygenase-2 levels in the skin and interleukin (IL)-4, IL-13, immunoglobulin E, and eosinophil levels in the blood were also performed.Results: EL systems were superior to conventional cream, revealing greater flux values in a permeation study. The addition of Tat peptide further increased the skin permeation of HST. In an efficacy study with AD-induced NC/Nga mice, an HST-containing EL/T formulation brought a significant improvement in both skin severity score and immune-related responses for the levels of nitric oxide synthase, cyclooxygenase-2, IL-4, IL-13, immunoglobulin E, and eosinophils.Conclusion: A novel EL/T formulation was successfully developed for topical delivery of HST to treat AD.Keywords: hirsutenone, elastic liposomes, atopic dermatitis, NC/Nga mice, Tat peptide